Reducing the life cycle environmental impact of electric vehicles through emissions-responsive charging - Yuzhou Tang (Elsevier, 2021)
Summary: Electric vehicles (EVs) are currently being promoted to reduce transport emissions. We present a life cycle assessment of EV charging behaviors based on marginal emissions factors. For Great Britain, we find that electricity consumption accounts for the highest proportion of life cycle carbon emissions from EVs. We highlight the potential life cycle carbon emissions reduction brought by charging during periods when the grid mix produces relatively low emissions. While our study focuses on Great Britain, we have applied our methodology to several European countries with contrasting electricity generation mixes. Our analysis demonstrates that countries with a high proportion of fossil energy will have reduced benefits from deploying EVs, but are likely to achieve increased benefits from smart charging approaches. We conclude that using marginal emissions factors is essential to understanding the greenhouse gas impacts of EV deployment, and that smart charging tied to instantaneous grid emissions factors can bring benefits.